CRIMINAL LIABILITY FOR VIOLATION OF THE ORDER OF OBTAINING EVIDENCE AND THEIR ADMISSIBILITY IN CRIMINAL PROCEEDINGS - Лихова, Софія Яківна; Ланцедова, Юлія Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: to consider the possibility of improving the basic basic properties of evidence and the admissibility of information in such quality in proof, and also suggest a solution to the problems of criminal and other legal responsibility for the violation of the procedure for obtaining evidence. Research methods: comparative legal analysis, cognitive-analytical, etc. Results: proof should have an integral set of the following basic basic legal properties, such as their significance, good quality and reliability, and the violation of the procedure for obtaining evidence should bear the appropriate criminal and other legal responsibility for the guilty person and resulted in inadmissibility of this evidence only in the event of doubt in its reliability or in the event if this information lacks other main basic legal features of evidence. Discussion: it has been stated that national procedural legislation and case law based on it and related to equitable decisions in the event of recognition of information as inadmissible evidence under formal circumstances regarding incompliance with the procedure of obtaining evidence and in the event of the lack of doubt in its reliability violates legal status of victims and contradicts p. 2 of Art. 3 of the Constitution of Ukraine regarding the main duty of the state and its authorities to assert and ensure rights and freedoms of all citizens. In this aspect, the problem of bringing to criminal responsibility for coercion to testify during interrogation or deliberate commission by a law enforcement officer of actions that are clearly beyond the limits of the rights or powers granted to him, are considered if they significantly damaged the rights of the person protected by law and the compulsion to testify was carried out at carrying out other investigative actions related to receiving testimony from a person. Particular attention is drawn to the qualification of torture in the context of the requirements of Art. 3 «Prohibition of Torture» of the Convention for the Protection of Human Rights and Fundamental Freedoms and the Practice of the European Court of Human Rights in relation to the definition of three stages of prohibited treatment.